STUDY OF THE SEVERITY AND EARLY ANTIVIRAL TREATMENT FOR THE DURATION OF THE RECOVERY COVID-19 PATIENTS - Susilo, Rinto; _, Tomi; Hidayati, Nur Rahmi; Asmarandani, Deani; Fadhilah, Daffa (Universitas Muhammadiyah Magelang, 2023)
Late antiviral treatment can potentially cause the Covid-19 virus to replicate very quickly, so it is necessary to understand antiviral drugs and optimize treatment for Covid-19 patients. The study aimed to determine the correlation between the severity, speed of administration of antivirals, and the recovery time of Covid-19 patients. This type of research is an observational study with retrospective data collection on 94 Covid-19 medical records at “X” Hospital Cirebon from 316 populations in June-July 2021 according to inclusion criteria. The data analysis used was univariate and bivariate using Spearman's Rho. The 55–59-year age group (28.7%) was the most infected with Covid-19. There are more males than females (52.1% vs 47.9%). Favipiravir therapy (43.6%) was given the most. Moderate severity (74.5%) had the highest proportion. The speed of administration of antivirals was most initiated at 5-8 days (42.6%) after the onset of symptoms. The maximum recovery time for Covid-19 patients is 13-18 days (58.5%). A strong positive correlation between the speed of giving antivirals to the recovery time of Covid-19 patients (sig. 0.000) and the correlation coefficient of 0.659. Does not show a correlation between the severity of recovery time (sig. 0.113) and speed of antiviral administration to the severity of Covid-19 patients (sig. 0.297). There is a correlation between the early antiviral treatment and the recovery time of Covid-19 patients; the earlier antiviral therapy is given, the faster it will heal.